Konsep Kebajikan dan Perilaku Manusia dalam Dua Mazhab Teologi Islam - Yoyo Rodiya; Muhammad Salimi; Muhammad Azka Maulana (Jurnal An-Nufus, 2021)
This study discusses two key concepts, namely the concepts of free-will and pre-destination, in two schools of Islamic theology, Jabariyyah and Qadariyyah, which emerged after the death of the Prophet Muhammad. Both schools of Islamic theology have their own advantages and disadvantages. The understanding of the two schools is very extreme and contradictory. Globally, the difference between Jabariyah and Qadariyah schools of thought is that Jabariyah views humans as very weak creatures, not having the strength and ability to determine their will and actions. On the other hand, Qadariyah considers that humans have their own strengths and abilities to determine all their wills and actions. The results of this study indicate that the two contradictory thoughts need to be integrated in order to produce a common ground to avoid extremism (ghuluw) in understanding and implementing the teachings of Islam.